STRIDE II: A Water Strider-inspired Miniature Robot with Circular Footpads. (10th June 2014) - Ozcan, Onur; Wang, Han; Taylor, Jonathan D.; Sitti, Metin
Water strider insects have attracted the attention of many researchers due to their power-efficient and agile water surface locomotion. This study proposes a new water strider insect-inspired robot, called STRIDE II, which uses new circular footpads for high lift, stability and payload capability, and a new elliptical leg rotation mechanism for more efficient water surface propulsion. Using the advantage of scaling effects on surface tension versus buoyancy, similar to water strider insects, this robot uses the repulsive surface tension force on its footpads as the dominant lift principle instead of creating buoyancy by using very skinny (1 mm diameter) circular footpads coated with a superhydrophobic material. The robot and the insect propel quickly and power efficiently on the water surface by the sculling motion of their two side-legs, which never break the water surface completely. This paper proposes models for the lift, drag and propulsion forces and the energy efficiency of the proposed legged robot, and experiments are conducted to verify these models. After optimizing the robot design using the lift models, a maximum lift capacity of 55 grams is achieved using 12 footpads with a 4.2 cm outer diameter, while the robot itself weighs 21.75 grams. For this robot, a propulsion efficiency of 22.3% was measured. The maximum forward and turning speeds of the robot were measured as 71.5 mm/sec and 0.21 rad/sec, respectively. These water strider robots could be used in water surface monitoring, cleaning and analysis in lakes, dams, rivers and the sea.